Tidal evolution of massive, eccentric binary systems: Effects of resonance locking - Savonije, G; Witte, MG (2001)
Contrary to what is generally assumed, resonant tidal interaction with gravity modes seems a common phenomenon during the evolution of massive eccentric binary systems. This is because non-resonant low order retrograde orbital harmonics drive weak high order harmonics up into resonance until the resonant interaction counterbalances the driving and the prograde harmonic gets locked. This frequently occurring near-resonant tidal interaction gives rise to strongly enhanced tidal evolution whereby large orbital eccentricities decay to small values in only a few million years in systems with orbital periods less than about 10 days.